A dynamic reframing of the social/personal identity dichotomy. (February 2022) - Walker, Benjamin W.
For decades, scholars in organizational and social psychology have distinguished between two types of identity: social and personal. To what extent, though, is this dichotomy useful for understanding identities and their dynamics, and might a different approach facilitate deeper insight? Such are the guiding questions of this article. I begin by reviewing framings of the social/personal identity dichotomy in organizational psychology, and tracing its origins and evolution in social psychology. I then evaluate the strengths and limitations of this dichotomy as a tool for understanding identities. In an attempt to retain the dichotomy's strengths and overcome its limitations, I present a modified conceptualization of the social and personal dimensions of identity, one that defines these dimensions based on psychological experience (not identity content), and treats them as two independent continua (not two levels of a dichotomy, or opposing ends of a continuum) that any given identity varies along across contexts. Plain language summary: A single person can identify with lots of different aspects of their life: their family, community, job, and hobbies, to name but a few. In the same way it helps to group different items in a shop into sections, it can be helpful to group the different identities available to people into categories. And for a long time, this is what researchers have done: calling certain identities "social identities" if based on things like race and culture, and "personal identities" if based on things like traits and habits. In this paper, I explain that for various reasons, this might not be the most accurate way of mapping identities. Instead of categorizing them based on where they come from, I suggest it's more helpful to focus on how identities actually make people feel, and how these feelings change from one moment to the next. I also point out that many identities can make someone feel like a unique person and part of a broader group at the same time. For this reason, it's best to think of the "social" and "personal" parts of an identity not as opposites—but simply different aspects of the same thing.